Relationship between physical activity and body composition in college students - Almeida-de-Souza, Juliana (2014)
Overweight is associated with the higher prevalence of chronic diseases. The daily practice of exercise lead to decrease the body fat percentage, the prevention and treatment of obesity associated with diseases. The aim of this study is to assess the infl uence of physical activity in body composition of college students. The study included 271 students (91 men, 180 women), the average age being 21.6 ± 2.8 years old. Body fat percentage was obtained by bioelectrical impedance analysis and the physical activity by the International Physical Activity Questionnaire. Data were analysed using descriptive statistics, Kruskal–Wallis, ANOVA and Turkey test, in statistical software SPSS vs. 18.0. The results showed that the moderate level of physical activity was more prevalent among students of both genders. In males, we found that physical activity infl uenced body fat % (p = 0.03). A multiple comparison analysis identi- fi ed a statically signifi cant difference (p = 0.005) between fat % of individuals classifi ed with a low level (18.0 ± 5.6%) and those with a vigorous level (14.5 ± 3.7%) of physical activity. The opposite was found for female, didn’t exist statically signifi cant differences between physical activity and body fat %.